Prof. dr. Franc Pediček in njegova prizadevanja za uveljavitev strokovne in znanstvene misli na področju telesne kulture oziroma športa - Berčič, Herman (Šport (Ljubljana), 2013)
Prof. Dr Franc Pediček was a great thinker and one of the most prominent pedagogues of his time. Throughout his academic life he provided an anthropological rationale to the development of pedagogy and also other expertand scientific areas. In terms of anthropology, i.e. the science of humans, he investigated the field of physical culture, i.e. sport along with its narrower domains - physical education, sport and sport recreation. As an outstanding and also critical pedagogue and indomitable advocate of a different approach to young generations he imparted his vast knowledge in philosophy, pedagogy, psychology and ethics to the students of the then Institute for Physical Education and later the short-cycle college and the College of Physical Culture in Ljubljana. His progressive ideas and intertwining of new findings with the specific domains of physical culture, namely physical education, elite sport and sport recreation, left indelible impressions on this segment of human life and creation. He was among the first to call for scientific research into physical culture, i.e. sport, incessantly advocating the anthropological facet of the study of all types of sports.
Keywords: anthropology; antropologija; pedagogi; Pediček, Franc, 1922-2008; physical culture; scientific method; scientific research; sport; šport; telesna kultura; znanstveno raziskovanje